Business Unusual : Accelerating Progress Towards Universal Health Coverage - World Bank (World Bank, Washington, DC, 2018)
At present rates, the global 2030 Universal Health Coverage (UHC) targets under the United Nations Sustainable Development Goals will not be met. Urgent action is needed to speed progress in the two dimensions of UHC, health service coverage and financial protection, and to ensure that no one is left behind. What can be done? First, countries can learn from past experience. This report identifies a set of factors common among countries that made outstanding progress on selected service coverage and financial protection indicators between 2000 and 2015. By adapting proven approaches to their own settings, and by addressing stubborn implementation bottlenecks, countries can accelerate progress towards UHC. Second, even as they benefit from models of success, countries must prepare to manage deeper health system transformation now on the horizon. Spurred by economic, technological, demographic, and epidemiologic forces, these transformations will reshape the landscape in which countries pursue their 2030 UHC goals, creating new risks but also opportunities.